2016
DOI: 10.1007/s12072-015-9700-7
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib combined with transarterial chemoembolization in patients with hepatocellular carcinoma: a meta-analysis and systematic review

Abstract: In summary, our meta-analysis found that TACE + sorafenib can improve TTP. We did not find the combined therapy improved OS. Additional randomized controlled studies are necessary to further investigate the clinical benefit of TACE + sorafenib in treating advanced HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 34 publications
1
22
1
Order By: Relevance
“…Several other studies have also reported that patients treated with combination therapy had longer survival duration [14-16]; however, survival outcomes in these studies, in which the study populations comprised partly or almost entirely BCLC stage B patients, were compared with those of TACE monotherapy. Although our study yielded results similar to those of the above-mentioned studies and included a larger number of patients receiving combination therapy, the current meta-analyses found that combination therapy only prolonged the time-to-progression but not overall survival [17, 18]. Therefore, further prospective randomized controlled trials are needed to confirm the clinical benefit of the combination therapy of TACE and sorafenib.…”
Section: Discussionsupporting
confidence: 62%
“…Several other studies have also reported that patients treated with combination therapy had longer survival duration [14-16]; however, survival outcomes in these studies, in which the study populations comprised partly or almost entirely BCLC stage B patients, were compared with those of TACE monotherapy. Although our study yielded results similar to those of the above-mentioned studies and included a larger number of patients receiving combination therapy, the current meta-analyses found that combination therapy only prolonged the time-to-progression but not overall survival [17, 18]. Therefore, further prospective randomized controlled trials are needed to confirm the clinical benefit of the combination therapy of TACE and sorafenib.…”
Section: Discussionsupporting
confidence: 62%
“…Three prior systematic reviews compared the effect of sorafenib plus TACE with TACE alone in patients with advanced HCC [17,20,21]. They all found that sorafenib combined with TACE significantly prolonged the time to progression, but did not significantly improve overall survival in patients with advanced HCC, which was inconsistent with our findings.…”
Section: Discussioncontrasting
confidence: 97%
“…However, the reviews differed with regard to the pooled overall survival and time to progression. Peng et al reported that sorafenib significantly improved the overall survival and time to progression(TTP) of advanced HCC [18], while Wang et al demonstrated that TTP was significant longer in the sorafenib plus TACE group than in the TACE alone group, but differences in overall survival between the two groups did not reach significance [21]. This systematic review aims to investigate the efficacy and safety of sorafenib in the management of unresectable HCC, and uses the GRADE system to evaluate the evidence value.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of the results from the GIDEON trial showed that TACE + SOR was a well-tolerated and viable therapeutic approach for the treatment of HCC 31. A meta-analysis showed that TACE + SOR improved TTP compared to TACE alone, but this analysis did not show any improvement in OS,32 while meta-analyses by Zhang et al21 and Hu et al9 showed that TACE + SOR improved both OS and TTP compared with TACE alone. This discrepancy could be due to a number of factors, including the studies being included and the populations being studied.…”
Section: Discussionmentioning
confidence: 99%